2014
DOI: 10.3389/fpsyg.2014.00719
|View full text |Cite
|
Sign up to set email alerts
|

The development of contour processing: evidence from physiology and psychophysics

Abstract: Object perception and pattern vision depend fundamentally upon the extraction of contours from the visual environment. In adulthood, contour or edge-level processing is supported by the Gestalt heuristics of proximity, collinearity, and closure. Less is known, however, about the developmental trajectory of contour detection and contour integration. Within the physiology of the visual system, long-range horizontal connections in V1 and V2 are the likely candidates for implementing these heuristics. While post-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 108 publications
2
12
0
Order By: Relevance
“… 37 , 38 Infants develop the ability to individuate objects by shape and size by 4.5 months, 39 while the ability to integrate contours or edges emerges later around 6 months. 40 , 41 By 5 months most infants have fusion and stereopsis, followed by rapid development to reach adult levels by 6–7 months of age; 35 meanwhile, the development of spatial acuity continues to improve well past infancy ( Figure 1 ). 31 , 42 Normal time course for the development of spatial visual functions is not preprogrammed but instead is experience-dependent and abnormal vision can have a profound effect on the maturation of these functions.…”
Section: Stage 1: the First Year Early Maturation Of Vision And The mentioning
confidence: 99%
“… 37 , 38 Infants develop the ability to individuate objects by shape and size by 4.5 months, 39 while the ability to integrate contours or edges emerges later around 6 months. 40 , 41 By 5 months most infants have fusion and stereopsis, followed by rapid development to reach adult levels by 6–7 months of age; 35 meanwhile, the development of spatial acuity continues to improve well past infancy ( Figure 1 ). 31 , 42 Normal time course for the development of spatial visual functions is not preprogrammed but instead is experience-dependent and abnormal vision can have a profound effect on the maturation of these functions.…”
Section: Stage 1: the First Year Early Maturation Of Vision And The mentioning
confidence: 99%
“…The visual system's ability to group discrete elements with similar orientation into a continuous contour that can be detected is known as contour integration (Field et al, 1993). Neural correlates of contour integration include horizontal connections and feedback connections (Taylor et al, 2014;Pak et al, 2020). Earlier studies based on computational network models proposed to understand illusory contour responses suggest that neurons in higher order visual areas such as V2 might pool orientation selective feedforward inputs from lower order areas like V1 (Mignard and Malpeli, 1991).…”
Section: Development Of Contour Integration Perceptionmentioning
confidence: 99%
“…Behavioral evidence supporting mechanisms of contour detection suggest that this function is present in the early stages of development (Field et al, 1993;Kovács et al, 1999;Hipp et al, 2014;Taylor et al, 2014), however, full maturation of this function requires years of visual experience. Kovács et al (1999) reported that children younger than 3 years of age were unable to identify a coherent contour defined by a circular ring of gabor patches embedded in noise, and their ability to perform the task improved into their teenage years.…”
Section: Development Of Contour Integration Perceptionmentioning
confidence: 99%
“…Human visual system is very adept at this task. Psycho-visual analysis has revealed that from a very small age, humans are able to detect contour segments and group them together based on their context [1] [2] which forms an integral part of object localization, detection and eventually, recognition. Moreover, visual attention process is understood to consist of two sequential steps; a faster initial step which is task-independent and focuses on the most appealing parts of the scene followed by a later, comparatively slower step which searches the visual space for a particular object of interest [3].…”
Section: Introductionmentioning
confidence: 99%